IMPROVING STUDENTS’ MOTIVATION OF SPEAKING BY USING GAME CARD TOURNAMENT The Case of Grade 7 Students of State Junior High School 6 Tegal, in the Academic Year of 2012/2013 (English Education Journal, 2013)
Speaking became one of the main skills and compulsory learned by the students of Junior High School. It was stated in the syllabus and formulated in standard competence and basic competence. The objective of this classroom action research was to overcome the problem faced by the teacher in carrying out teaching learning process of speaking, students’ low motivation to speak. The problems were that 1) low pronunciation ability 2) poor vocabulary items mastery 3) doubt and confusion about expressions usage.  This classroom action research applied Game Card Tournament to improve students’ motivation to speak. When students played Game Card Tournament, they not only played for fun but also practiced pronunciation, learned more about vocabulary and practiced speaking about occupation using acceptable expressions. Moreover video clips and power point presentation were also implemented to practice pronunciation, expressions and vocabulary. The motivation of students improved when they expressed their idea freely during playing the game. Since the Cards used to play consisted of pictures and illustration of job’s description, students were more motivated to speak. As the students improved their motivation to speak, the teaching learning process about occupation became more meaningful and interesting and of course students’ achievement improved as well.